Are ethical committees reliable? - Hotopf, M (1995)
This paper aims to assess the reliability of Local Research Ethical Committees (LREC), using a genuine research proposal which was sent to six LRECs. The main outcome criteria were modifications demanded by committees and the degree of agreement between them. All but one of the committees demanded some change in the proposal. None of the committees asked for the same changes. Our conclusion is that LRECs are highly variable.